Dog owners’ awareness of the zoonotic potential of endoparasites of their pets and potential risk factors for humans - Ristić, Marko; Višnjić, Aleksandar (Frontiers in Animal Science, 2025)
AimThe aim of this research was to establish the attitudes of dog owners in Serbia towards caring for their dogs with particular emphasis on veterinary care and parasite control.MethodsThe study presents a social-medical approach to the problem of contamination of public urban areas in the city of Niš with intestinal parasites from dog faeces. Accordingly, a survey regarding attitudes, behaviour and the level of education of dog owners and people staying in the parks of the city of Niš was conducted. A total of 350 dog owners were surveyed. 198 (56.57%) of them were female, and 152 were male (43.43%).ResultsThe largest number of respondents take their dog to a veterinarian when they have doubts about their dog’s health (22.3%). The most common reason for visiting a veterinarian is vaccination. The largest number of owners give tablets against internal parasites every six months (29%), 22% of owners every 3 months, and 21% of owners once a year. The largest number of owners treat their dogs against fleas and other external parasites every 6 months (22%), while 21% of owners do it once a year. A third of dog owners have their dogs vaccinated against infectious diseases every year. The largest number of surveyed owners (62%) travel with their dogs, half of them even sleep next to their pets, and a third of them take their dog to the pet groomer. Regular coprological examinations of dogs are carried out by only a fifth of the surveyed owners. More than a half of the surveyed dog owners regularly use both anti-endoparasites and anti-ectoparasites to treat their dogs.ConclusionMain parks in the city of Niš, as well as other urban areas, seem to be the potential sources of zoonotic parasites. The results of this study show that the majority of dog owners are not adequately educated in terms of veterinary care requirements and parasite control.